External Reserve on Economic Growth in Nigeria - Nwosa, Philip Ifeakachukwu (Journal of Entrepreneurship, Business and Economics, 2017)
This study examined relationship between external reserves and economic growth in Nigeria from 1981 to 2014. The study used the Ordinary least squares econometric method of analysis. The result of the study showed that external reserves had positive and significant influence on the economic growth in Nigeria. Based on the major finding of this study, it was concluded that external reserve in Nigeria has over the period of study contributed positively and significantly to the growth of the economy. Thus, the study recommended the need for prudent management of Nigerian’s external reserves to ensure more growth and also that government should put in more policies that will enhance increased accumulation of external reserves. Research paper Keywords: External reserves, economic growth, OLS, Nigeria Reference to this paper should be made as follows: Nwosa, P. I. (2017). External Reserves on Economic Growth in Nigeria, Journal of Entrepreneurship, Business and Economics , 5 (2), 110–126.